Managing adverse effects by dose reduction during routine treatment of locally advanced basal cell carcinoma with the hedgehog inhibitor vismodegib: a single centre experience. (17th December 2018) - Woltsche, N.; Pichler, N.; Wolf, I.; Di Meo, N.; Zalaudek, I.
Abstract : Linked article: This article is commented on by M. Scalvenzi et al ., pp. e146–e147 in this issue. To view this article visithttps://doi.org/10.1111/jdv.15469 .